2015
DOI: 10.1093/jnci/djv189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antiretroviral Therapy on Kaposi’s Sarcoma–Associated Herpesvirus (KSHV) Transmission Among HIV-Infected Zambian Children

Abstract: Our data suggest that early ART and prevention of immune suppression reduce the risk of KSHV acquisition among HIV-infected children in an area where both viruses are highly endemic. This study highlights the importance of programs in Africa to provide children with ART immediately after HIV infection is diagnosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…Recent studies demonstrated that HIV-infected children have a higher risk of co-infection with HHV-8 compared to HIV-uninfected children [16,17]. An observational study from Zambia suggested that in HIV-infected children receiving cART the risk of HHV-8 infection was similar to HIV-uninfected children [17].…”
Section: Epidemiology Of Cancer In Hiv-infected Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies demonstrated that HIV-infected children have a higher risk of co-infection with HHV-8 compared to HIV-uninfected children [16,17]. An observational study from Zambia suggested that in HIV-infected children receiving cART the risk of HHV-8 infection was similar to HIV-uninfected children [17].…”
Section: Epidemiology Of Cancer In Hiv-infected Childrenmentioning
confidence: 99%
“…Recent studies demonstrated that HIV-infected children have a higher risk of co-infection with HHV-8 compared to HIV-uninfected children [16,17]. An observational study from Zambia suggested that in HIV-infected children receiving cART the risk of HHV-8 infection was similar to HIV-uninfected children [17]. In contrast, in HIV-infected children not receiving cART the risk of acquiring HHV-8 was six-times higher compared to HIV-uninfected children (incidence rate ratio 5.97, 95%CI 3.13–11.41) [17].…”
Section: Epidemiology Of Cancer In Hiv-infected Childrenmentioning
confidence: 99%
“…Indeed, herpesviruses are normally and predominantly “silently” transmitted from mother to child. Mother-to-child transmission in infancy is the predominant mode for acquiring Epstein-Barr Virus ( EBV ) and Kaposi sarcoma-associated herpesvirus ( KSHV ) in endemic healthy populations[1,2]. …”
Section: Introductionmentioning
confidence: 99%
“…in the absence of active HIV replication and despite a reasonable number of CD4 cells (>200). These patients tend to be older men and may represent the intersection of incomplete immune repertoire restoration after HIV exposure, long-term immune activation due to microbial translocation, and diminished immune function due to aging.In Sub-Saharan Africa, KS is also observed in children that acquired both HIV and KSHV at infancy from their mother[1]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation